Pengaruh Persepsi Manfaat, Kemudahan, Kepercayaan, dan Keamanan terhadap Keputusan Penggunaan Byond by BSI pada Dosen UIN STS Jambi - Nurhaliza, Siti; Fusfita, Nurlia; Sari Putri, Nurrahma (ARZUSIN, 2026)
Various systemic and psychological factors influence the adoption and increased use of mobile banking services in the university environment. This study aims to investigate the influence of perceived usefulness, perceived ease of use, perceived trust, and perceived security on the use of Byond by BSI among lecturers at UIN STS Jambi. This study used a descriptive quantitative approach involving lecturers at UIN STS Jambi as respondents. Data were collected through a Likert-scale questionnaire distributed to lecturers who participated in the study. Data were analyzed through validity and reliability tests, R-square evaluation, and hypothesis testing using the bootstrapping technique with the assistance of SmartPLS 4.1.1.6 software. The results show that perceived usefulness has a positive and significant effect on the decision to use Byond by BSI. Meanwhile, perceived ease of use, trust, and security showed positive but insignificant effects on the decision to use Byond by BSI. These findings indicate that the use of Byond by BSI among lecturers at UIN STS Jambi is more strongly influenced by perceived usefulness, whereas ease of use, trust, and security have not yet become significant determining factors. This condition is related to the use of Byond by BSI, which largely functions as a payroll account and has not yet fully become the main account for transactions. This study contributes to the development of research on the adoption of Islamic mobile banking services and provides practical implications for Bank Syariah Indonesia in improving the quality, reliability, and utility value of Byond by BSI.